Characterizing Community-Based Mental Health Services for Children with Autism Spectrum Disorders and Disruptive Behavior Problems - Brookman-Frazee, Lauren I. (Springer US, 2010)
This study describes the characteristics of children with autism spectrum disorders (ASD) with disruptive behavior problems served in community-based mental health clinics, characterizes psychotherapy process and outcome, and examines differences between children with ASD and a non-ASD comparison group. Results indicate that children with ASD served in this setting are high functioning and diagnostically complex. Certain research-based behavioral and cognitive behavioral psychotherapeutic strategies were observed frequently, while parent training strategies and active teaching strategies were observed less frequently. The intensity or thoroughness with which strategies were pursued was relatively low. Outcome analyses indicate improvement in child symptoms and family functioning. Treatment delivery and outcome were similar for children with and without ASD. These findings represent the first detailed observational data characterizing community-based mental health services for children with ASD.